Analisa Strategi Implementasi Green Computing pada ITS NU Sriwijaya Sumatera Selatan - Bella Rizninda Putri; Tania Galuh; Beni Brahara (Universitas Multi Data Palembang, 2023)
Educational activities are inseparable from the use of Information and Communication Technology (ICT). ICT is not only limited to supporters but also a competitive advantage in the world of education. In addition to the convenience gained from the use of ICT devices there is an environmentally unfriendly effect produced by the influence of energy consumption used during the operation of ICT equipment. To overcome this problem, it is important that there are efforts and strategies that must be carried out in order to achieve Green Computing in daily operations at the ITS NU Sriwijaya. In this study, the authors analyzed strengths, weaknesses, opportunities, and risks on campus using a SWOT analyst. The results showed that the situation of ITS NU Sriwijaya is now in a grow position. The strategies developed include SO (Strength-Opportunitiy) making strategies that use power to seize opportunities, namely: using ICT devices with a long service life, virtualization, increasing the use of laptops compared to computers, developing E-Learning-based learning systems, expanding ICT infrastructure as needed, and developing the quality of human resources through training and workshops around ICT.